2020
DOI: 10.18261/issn.2387-5984-2020-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Trygghet uten særomsorg?

Abstract: Vitenskapelig publikasjon Trygghet uten saeromsorg? Helsepersonells perspektiv på trygghet og sikkerhet for sørsamiske brukere av helse-og omsorgstjenester Safety without special care? Health personnel's perspectives on safety and security for South Sami users of health and care services

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Mehus et al [ 42 ] found that bilingual health care staff in Norway were able to use their competency in Western medicine and familiarity with the majority health care system to provide culturally safe care for the Sámi population, illustrating a form of cultural brokerage. Other examples of cultural brokerage for Sámi in Norway through use of Sámi staff are illustrated by Andreassen Devik and Olsen 2020 [ 43 ] based on municipal care for elderly Sámi, and Larsen [ 13 ], as who studied relatives to Sámi patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mehus et al [ 42 ] found that bilingual health care staff in Norway were able to use their competency in Western medicine and familiarity with the majority health care system to provide culturally safe care for the Sámi population, illustrating a form of cultural brokerage. Other examples of cultural brokerage for Sámi in Norway through use of Sámi staff are illustrated by Andreassen Devik and Olsen 2020 [ 43 ] based on municipal care for elderly Sámi, and Larsen [ 13 ], as who studied relatives to Sámi patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Mehus et al [ 42 ] mean that in order to achieve cultural safety on a group level, all health professionals who meet Sámi patients and families should reflect on the extent to which cultural competence and sensitivity are present in their workplaces. Andreassen Devik and Olsen [ 43 ] conclude that cultural sensitivity is even a prerequisite for person-centered care for Sámi. While the term cultural sensitivity is most often used in English-language literature, its use is not always consistent [ 44 ], and in our prior work, we have used the term cultural humility [ 45 ] instead.…”
Section: Discussionmentioning
confidence: 99%